Flow structures and circulation due to meandering geometry in a stratified sea strait - Ozturk, Mehmet (ELSEVIER, 2022)
Combining with local topography (i.e., the presence of a bar or a sill on the bottom and the shape of the coastline), the meandering geometry of straits, which have more complex geomorphological formations compared to rivers, reveals different circulation patterns in the coastal region and central part of the strait. Identifying circulation patterns in meanders is crucial to managing those waterways in several aspects (i.e. monitoring the transport of contamination, wastewater outfall, etc.). In the present study, the flow circulations in some meanders of a strait (the Bosphorus), which presents a two-layered flow, are analyzed using the calibrated 3D model. Each of the four selected meanders has a unique shape: 1) expansion on both sides, 2) expansion on one side, 3) with a constant width, and 4) an estuary connected from one side. The results showed the decisive role of some characteristic morphological formations (i.e. headland, bars on the bottom, the shape of coastline) in creating reversing flow in a meander rather than adverse along channel pressure gradient due to the sudden expansion. While extreme water level differences between both entrances of the strait reveal unidirectional flow in the main channel, the reversals may develop in the shallowness of the meanders depending on the coastline shape (e.g. smoothness), presence of a local bar, and the presence of a headland. Besides this, in the case of a meander that has expansion at both sides, the flow separates from the main channel and circulates in opposite direction either clockwise or counterclockwise in the expanded sections. The annual flow profiles show a notable difference between the main channel and the coastal part of the meanders for a significant amount of time. For the low composite Froude numbers (G(2)) around or less than 0.3, the main channel flow is two-layered with the upper layer flowing south and the lower layer flowing north. In the shallowness of the expansions, however, it is unidirectional. For higher G(2)s (> 0.6), however, it is unidirectional both in the main channel and in the expansions of the meanders. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: Sea straits; Meandering geometry; The Bosphorus; Flow circulation; Hydrodynamics; 3D numerical modeling; SECONDARY CURRENTS; WATER EXCHANGE; BOHAI STRAIT; ISTANBUL; TRANSPORT; SYSTEM; RIVER; VARIABILITY; HYDRAULICS; SEDIMENT; Environmental Sciences & Ecology; Marine & Freshwater Biology